Action type geometrical equivalence of representations of groups - Plotkin, B.; Tsurkov, A. (Algebra and Discrete Mathematics, 2005)
In the paper we prove (Theorem 8.1) that there
exists a continuum of non isomorphic simple modules over KF₂,
where F₂ is a free group with 2 generators (compare with [Ca]
where a continuum of non isomorphic simple 2-generated groups is
constructed). Using this fact we give an example of a non action
type logically Noetherian representation (Section 9).